Viruses Associated with Fig Mosaic Disease in Different Fig Varieties in Montenegro - Jelena Latinović; Sebastjan Radišek; Milija Bajčeta; Jernej Jakše; Nedeljko Latinović (The Plant Pathology Journal, 2019)
Symptoms of fig mosaic disease have been noticed on leaves of fig (Ficus carica) for several decades, in Montenegro. In 2014, leaf samples were collected from trees of six fig cultivars in a plantation located in the main fig-producing area of Montenegro, to study the disease. After RNA isolation, samples were tested by RT-PCR for detection of nine fig viruses and three viroids. Four viruses were detected: fig leaf mottle-associated virus 1 (FLMaV-1), fig mosaic virus (FMV), fig mild mottle-associated-virus (FMMaV) and fig badnavirus 1 (FBV-1). Most of the viruses were present in mixed infections. The amplicons of the viruses were directly sequenced from both directions. A BLAST search of these sequences revealed sequence identities with their closest counterparts at GenBank of 92, 97, 92 and 100%, for FLMaV-1, FMV, FMMaV and FBV-1, respectively. Different responses in symptom expression due to the various virus combinations detected have been demonstrated. Variety Sušilica had the least symptom expression, with only one virus (FBV-1) found. Considering that the production of figs in Montenegro is increasing and has a substantial relevance in this geographic location, the results indicate that more attention should be given to improving the phytosanitary condition of fig trees in the country.